Egyptian Pediatric Guidelines for the Management of Children with Isolated Thrombocytopenia Using the Adapted ADAPTE Methodology-A Limited-Resource Country Perspective - Galila Mokhtar; Ashraf Abdelbaky; Amira Adly; Dina Ezzat; Gehan Abdel Hakeem; Hoda Hassab; Ilham Youssry; Iman Ragab; Laila M. Sherief; Marwa Zakaria; Mervat Hesham; Niveen Salama; et al. (MDPI AG, 2024)
Background: Thrombocytopenia is a prevalent presentation in childhood with a broad spectrum of etiologies, associated findings, and clinical outcomes. Establishing the cause of thrombocytopenia and its proper management have obvious clinical repercussions but may be challenging. This article provides an adaptation of the high-quality Clinical Practice Guidelines (CPGs) of pediatric thrombocytopenia management to suit Egypt's health care context. Methods: The Adapted ADAPTE methodology was used to identify the high-quality CPGs published between 2010 and 2020. An expert panel screened, assessed and reviewed the CPGs and formulated the adapted consensus recommendations based on the best available evidence. Discussion: The final CPG document provides consensus recommendations and implementation tools on the management of isolated thrombocytopenia in children and adolescents in Egypt. There is a scarcity of evidence to support recommendations for various management protocols. In general, complete clinical assessment, full blood count, and expert analysis of the peripheral blood smear are indicated at initial diagnosis to confirm a bleeding disorder, exclude secondary causes of thrombocytopenia and choose the type of work up required. The International Society of Hemostasis and thrombosis-Bleeding assessment tool (ISTH-SCC BAT) could be used for initial screening of bleeding manifestations. The diagnosis of immune thrombocytopenic purpura (ITP) is based principally on the exclusion of other causes of isolated thrombocytopenia. Future research should report the outcome of this adapted guideline and include cost-analysis evaluations.